Development, implementation, and experimental outdoor evaluation of quadcopter controllers for computationally limited embedded systems. (2021) - Paredes, Juan; Sharma, Prashin; Ha, Brian; Lanchares, Manuel; Atkins, Ella; Gaskell, Peter; Kolmanovsky, Ilya
Abstract: Quadcopters are increasingly used for applications ranging from hobby to industrial products and services. This paper serves as a tutorial on the design, simulation, implementation, and experimental outdoor testing of digital quadcopter flight controllers, including Explicit Model Predictive Control, Linear Quadratic Regulator, and Proportional Integral Derivative. A quadcopter was flown in an outdoor testing facility and made to track an inclined, circular path at different tangential velocities under ambient wind conditions. Controller performance was evaluated via multiple metrics, such as position tracking error, velocity tracking error, and onboard computation time. Challenges related to the use of computationally limited embedded hardware and flight in an outdoor environment are addressed with proposed solutions.